The Effect of Drying Methods on The Quality of Dragon Fruit Skin Tea - Ilmannafian, Adzani Ghani; Kiptiah, Mariatul; Darmawan, Muhammad Indra (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2024)
As a co-product, dragon fruit peels still contain polyphenols that can be used as a tea product alternative, requiring an appropriate drying process. Therefore, it is necessary to find a suitable drying method to obtain high-quality dragon fruit peels as tea product ingredients. The aim of this research is to determine the quality of dragon fruit skin tea with different drying methods. This research used an experimental method by using sun drying against the oven as a drying method in the drying stages of the dragon fruit tea skin making process. The dried fruit peels were then characterized by their tannin, flavonoid, vitamin C, and water contents, as well as their hedonic test scores. The results showed that the qualitative results of tannins and flavonoids in dragon fruit peel tea were positive (+), and the vitamin C content of the peel tea was higher when produced in sun-dried (6.6 mg/100g). On the contrary, the water content of dragon fruit peel tea was higher (7%) by oven drying. Based on hedonic tests, the panelists preferred dragon fruit peel tea produced by the sun drying.